Punishment System in Manusmrti and Dante Algieri’s Inferno of The Divine Comedy - Adhikari , Bhawani Shankar (Political Science Journal, 2025)
Both Inferno and Manusmriti use punishment as a means to instill fear in sinners, deterring them from committing wrongdoings in their earthly lives. In Inferno, punishments vary for different sinners, including politicians, and focus on rebirth as a consequence of earthly karma. In contrast, Manusmriti emphasizes punishment for thieves but does not include the concept of rebirth. Both texts aim to create fear to prevent sins and crimes, promoting an ideal society. The fear of divine punishment serves as a law, with Christianity in Inferno encouraging holiness and the concept of karma in Manusmriti paralleling this idea. The notion of being God-fearing in both texts guides individuals to lead virtuous lives to avoid future punishments. The given stanzas from Manusmriti and the lines and passages of Inferno have been adopted as the primary data and the related articles of various authors and waves have been taken as the secondary sources for the analysis of the punishment system in both of the texts. It has explored that both texts have generated the concept of God-fearing to lead the society without of sins and crimes.